(untitled) (Global Journal of Management and Business Research, 2017)
To make customer concerned with services and making long term relationship for the sustainable business organization there no time to compromise the expectation of customer and making available for. This study is related with the determinants of service quality factors concentrated on the specialized banks of Bangladesh. The empirically descriptive study has been conducted over the 75 respondents those are the customer of three specialized banks of Bangladesh. A well stuffed questionnaire was set to collect the primary data with considering each bank 25 respondents, it has been analyzed with taking the help of different statistical tools and encoding the data with Statistical Package for Social Sciences -SPSS (v-21).After Disseminating data it presents for the reader to make well perceive.